2010
DOI: 10.1159/000318017
|View full text |Cite
|
Sign up to set email alerts
|

Gene Promoter Methylation and Its Potential Relevance in Early Prostate Cancer Diagnosis

Abstract: Aims: We investigated hypermethylation of the glutathione S-transferase pi (GSTP1), retinoic acid receptor β2 (RARβ2), adenomatous polyposis coli (APC) and paired-like homeodomain transcription factor 2 (PITX2) gene promoters which could serve as a sensitive tool to indicate a risk of prostate cancer even in histologically tumor-free tissues. Methods: Tumor tissues and non-neoplastic tissues at variable distances from the tumor foci were retrieved from 25 formalin-fixed and paraffin-embedded prostatectomy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Consistent with most previous observations in prostate tumor tissue and blood ( Jeronimo et al, 2004;Yegnasubramanian et al, 2004;Reibenwein et al, 2007;Sunami et al, 2009;Steiner et al, 2010), we found that elevated DNA methylation levels in prostate tumor tissues were related to worse clinicopathological outcomes. Specifically, GSTP1, p16 (CDKN4A), and APC methylation levels were significantly associated with higher Gleason score.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with most previous observations in prostate tumor tissue and blood ( Jeronimo et al, 2004;Yegnasubramanian et al, 2004;Reibenwein et al, 2007;Sunami et al, 2009;Steiner et al, 2010), we found that elevated DNA methylation levels in prostate tumor tissues were related to worse clinicopathological outcomes. Specifically, GSTP1, p16 (CDKN4A), and APC methylation levels were significantly associated with higher Gleason score.…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, all three techniques used in our study identified weak ID4 methylation in benign prostatic tissues. Most likely, this observation may reflect an epigenetic field effect changing methylation [25,26], imprinting [27] and expression [28,29] of certain genes in cancer-carrying prostates. This field change could reflect morphologically inconspicuous tumor cells, changes in normal cells elicited by factors emanating from the actual cancer or a preneoplastic stage pervading the aging organ [30].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate tissue biopsy was able to detect GSTP1 methylation in 70.5% to 94% of PCa patients (Goessl et al, 2000;Jer-ó nimo et al, 2002;Steiner et al, 2010), with the variation between studies mostly due to variation in DNA methylation detection techniques.…”
Section: Discussionmentioning
confidence: 99%